PENGARUH PENGELOLAAN PEMBELAJARAN DAN PENGGUNAAN MODEL PEMBELAJARAN KONTEKSTUAL TERHADAP KINERJA GURU - Melly Safitri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2016)
Standard performance of teachers were working with students individually, learning management, utilization of learning methods, involve students in a variety of learning experiences, and the active leadership of the teacher. In this study the researcher formulated research problems: first, was there a positive effect and significant between learning management on the performance of teachers in MTs Patra Mandiri Palembang? The second, was there a positive effect and significant between the use of contextual learning model the performance of teachers in MTs Patra Mandiri Palembang? and thirdly, is there a positive effect and significant between the management of learning and use of contextual learning model on teacher performance together in MTs Patra Mandiri Palembang? , The researcher used a quantitative approach based on postpositivist paradigms which one of them was the relation of correlation (effect). The study also used quantitative research of double correlation with three variables: the variable bound (Y) called the performance of teachers, and two independent variables (X1 and X2) called learning management and use of contextual learning model. Statistics used were inferential statistics. The results of study were; first, there was a positive effect and significant between learning management toward the performance of teachers in MTs Patra Mandiri Palembang. Secondly, there was a positive effect and significant between the use of contextual learning model toward the performance of teachers in MTs Patra Mandiri Palembang. Thirdly, there was a positive effect and significant between the management of learning and the use of contextual learning model together on the performance of teachers in MTs Patra Mandiri Palembang.